Jihad in Sub-Saharan Africa: the role of digital media - Matusitz, Jonathan (Springer International Publishing AG, 2024)
This book examines how jihadist groups in sub-Saharan Africa have managed to advance their extremist agenda and recruit new followers thanks to digital media fueled by the information revolution since the dawn of the 21st century. This examination is based on a mixture of historical accounts, contemporary descriptions, case studies, theoretical applications, and an in-depth applied study (in the late chapters of the manuscript). An important conclusion is that the progress of jihadism in sub-Saharan Africa has been commensurate with the development and availability of digital media. This book breaks new ground in three ways. It is the first major academic work to devote most of its content exclusively to the use of digital media by jihadist groups in that region. Examples of jihadist digital media include social networking sites, online instructional videos, propaganda videos, and online jihadist magazines among others. Secondly, it provides detailed case studies of both well-knownAfrican groups (e.g., Al-Shabaab, Boko Haram) and lesser-known ones e.g., the Allied Democratic Forces in the Congo (which have, nevertheless, wreaked so much damage). Lastly, it is the first book to include an in-depth thematic analysis of online jihadist magazines Inspire, Dabiq, Rumiyah, and Gaidi Mtaani on their content dedicated to sub-Saharan Africa